ANTIOXIDANT ACTIVITY AND ISOLATION BIOACTIVE COMPOUNDS FROM ROSELLE (HIBISCUS SABDARIFFA) FROM VARIOUS METHODS AND DRYING TIME - ike sitoresmi mulyo purbowati; Sujiman Sujiman; Ali Maksum (AGROINTEK, 2019)
The focus of this study was to evaluate the effect of different drying methods and drying level on the bioactive compounds of roselle (Hibiscus sabdariffa L.)as antioxidant agent. The experiment has been conducted in cabinet dryer and by a direct exposure on sun light as weel as by using a green house effect panel with duration of driying: 1, 3, 5, 7 hours. The observed parameters were Colour, levels of anthocyanins,vitamin C, and free radical trapping capacity (DPPH). The data obtained were analyzed using analysis of variance (ANOVA) and further test DMRT (Duncant Multiple Range Test). The best results from these study was the cabinet drying with 7 h of drying time which have value for color (L, a*, b*), total anthocyanins, vitamin C, and antioxidant activity in respective order were 21.633; 6.80; 4.53; 3.22mg/100g; 1238.29mg/100g; 74,63%.